Late onset of apical hypertrophic cardiomyopathy in a former professional athlete subsequent to crush syndrome - Bianco, M.; Palmieri, V.; Vessella, T.; Cardillo, R.; Giorgiano, F.; Zeppilli, P. (Medicina dello Sport, 2011)
This paper describes the case of a former professional athlete who developed an apical hypertrophic cardiomyopathy (aHMC) apparently after a severe traumatic event at the age of 46 years. The aHCM can phenotypically appear in a relatively advanced age and the typical electrocardiographic abnormalities usually become visible before hypertrophy is evident at ultrasound or magnetic resonance imaging. Several studies show associations between various forms of surgical stress or trauma and myocardial lesions or cardiovascular disease, suggesting the role of sudden catecholaminergic stimulation in aHCM development in genetically predisposed subjects. Late onset of aHCM and late mean age of presentation may be an example of gene-environment interaction needed to reveal latent genotype manifestations.